Urban Experiences 'Beyond the West': Comparing Cities in Southern African and BRIC Countries. Issue 5 (3rd September 2017) - Potts, Deborah
Abstract : This article, which is based on a keynote speech for an urban panel at the Journal of Southern African Studies' conference, 'Southern Africa beyond the West', compares urban experiences in the region of southern Africa with those in the BRIC countries (Brazil, Russia, India and China). Urban processes are complex and wide ranging, and comparative analysis necessarily must focus on specific aspects. The focus here is on cities as places where people live and work and on their welfare and livelihoods. The analysis emphasises the importance of accounting for different starting points and thus of historical factors, policy environments, changing modes of production and ideologies. A key argument is that the concept of path dependence – including the timing of key developmental phases, such as the attainment of independence in relation to global shifts in economic ideology – helps to explain some of the differences in development policies and their impacts on urban livelihoods. It is also argued that while contemporary comparative analysis has been facilitated by the increased hegemony of capitalism, a key influence on the welfare of urban populations in the different countries under consideration has been the very varied ways in which states have been able, and have chosen, to intervene in market-determined outcomes in cities in BRIC countries and in southern Africa.